Disappearance of contralateral dominant neural activity of auditory cortex after single-sided deafness in adult rats. (14th September 2017) - Lee, Min Young; Kim, Doo Hee; Park, Su-Kyoung; Jun, Sang Beom; Lee, Yena; Choi, Jun-Jae; Yoo, Hyun Ji; Raphael, Yehoash; Oh, Seung-Ha
Highlights: Adult rats show plastic changes of both brain hemispheres after single side deafness. The plastic change can be summarized as the loss of normal contralateral dominance. Serial time point analysis suggests the two different phase after single side deafness. Abstract: Hearing loss in mature ears can cause functional reorganization of the auditory cortex. The functional reorganization is speculated to negatively affect the outcome of hearing rehabilitation. Therefore, once hearing loss occurs, it is important to provide auditory input before extensive reorganization in the auditory pathways. We investigated the neural plasticity in auditory cortex after single-sided deafness (SSD) in an adult rat model. The animals were divided into two groups: a normal hearing (NH) and the SSD group. The neural recordings of the SSD group were conducted at different time points (2, 4, 6 and 8 weeks) after cochlear ablation. The multi-unit activity was discriminated on the sum of spikes, peak amplitude, onset latency, peak latency, and responsive area based on the peak amplitude. The auditory cortical reorganization was observed after SSD. The contralateral dominance of peak amplitude and latency that normally occur in NH group were not present in the SSD group, replaced by higher amplitude and faster response in ipsilateral cortex. According to serial recordings at different time points after SSD, different phases in the response of the auditory cortex were speculated. Compared with normal hearing, alteration of contralateral dominance was observed because of the functional reorganization of the auditory cortex after SSD.